Sosialisasi Keamanan Jaringan: Bahaya Sniffing Pada Wifi Umum Terhadap Masyarakat - Jhazkia Putri Rizan; Marisha Setiyani; Kurnia Safitri; Nabila Putri Rahmalia; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The rapid growth of information technology has made people use the internet in many daily activities, such as communication, education, and financial transactions like mobile banking. However, using public Wi-Fi without proper security can be risky, especially due to threats like sniffing, where attackers can intercept and access users’ data without their knowledge. This outreach activity aims to increase public awareness about the dangers of sniffing and the importance of safe internet use. The method used was a descriptive approach, including material presentation, interactive discussions, question-and-answer sessions, and questionnaires. The activity was conducted with members of the Dawis group in RT 09/RW 07, Kranji Village, East Purwokerto. The results showed that all participants (100%) understood the material, with 62.5% agreeing and 37.5% strongly agreeing that it was easy to understand and relevant to their daily lives. Participants also became more aware of the risks of public Wi-Fi and learned simple ways to stay safe, such as avoiding access to important accounts, using HTTPS, and enabling two-factor authentication. In conclusion, this activity successfully improved digital security awareness and encouraged safer and more responsible internet use.